Pengaruh Self-Regulated Learning dan Motivasi Berprestasi Terhadap Perilaku Prokrastinasi Akademik Siswa - Achmad Robbi Fathoni; Erdina Indrawati (CV. Publikasi Indonesia, 2022)
Academic procrastination is a behavior carried out by students in the form of delaying work both to start and complete assignments for rational reasons, this can have a negative impact on achievement and also students' mental health. Academic procrastination is caused by several factors such as low self-regulated learning and achievement motivation and is moderated by social media addiction. This study aims to determine the effect of self-regulated learning and achievement motivation on academic procrastination, as well as the moderating effect of social media addiction. Participants in this study amounted to 134 students of SMPN class VIII, consisting of 54 boys and 80 girls with an age range of about 13 to 15 years. Data collection in this study used four scales, namely the academic procrastination scale, achievement motivation scale, academic self-regulated learning scale, and social media addiction scale. The academic procrastination scale has 17 items with a different power of 0.331-0.763 and a reliability of 0.907. The achievement motivation scale has 22 items with a different power of 0.337-0.740 and a reliability of 0.895. The academic self-regulated learning scale has 22 items with a power difference of 0.309-0.836 and a reliability of 0.928. The social media addiction scale has 5 items with a discrepancy of 0.371-0.556 and a reliability of 0.792. The data in this study were analyzed using the structural equation model technique. The results showed that 1) there was an effect of self-regulated learning on academic procrastination (p values ​​0.00<0.05); 2) there is no effect of achievement motivation on academic procrastination (p values ​​0.243 <0.05); 3) social media addiction did not affect the relationship between self-regulated learning and academic procrastination (p values ​​0.90<0.05); 4) social media addiction affects the relationship between achievement motivation and academic procrastination (p values ​​0.015<0.05).